Analysis of Spatio Temporal Change of Land Use of Chrysanthemum Farm in Semarang Regency Using Landsat Image 8 OLI - Priyadi Priyadi (Indonesian Journal of Computing and Modeling, 2018)
Agriculture is a business issue that has long existed and will likely continue to exist throughout the ages. Similarly, on the issue of agricultural land use chrysanthemum that needs to be developed method of analysis using technology approach and computer science. This research intends to analyze and develop effective and efficient methods of chrysanthemum land use. The satellite imagery data covering pre-processing, processing and post processing in this research is mostly done with QGIS software. Satelite image used in this research is LANDSAT 8 OLI and band used are band 6, bang 5, band 2 and band 8. Stages of working this research include image cutting in the research area of all bands and all temporal images involved in research, pansharpening using "Orfeo toolbox", image classification with "semi-automatic clasification", then completed with analysis of land use change using "molusce". The result of this research is spatio-temporal data of two images of land use chrysanthemum in April 2017 and August 2017. The result of mathematical research is a statistical table of changes of agricultural land use on two temporal of image used as research object. In addition to the two results of the analysis data, this study also describes the digital image analysis method of agricultural land use chrysanthemum which is expected to be useful for remote sensing research on other research object or extension to this research.